VERS LA RÉORGANISATION DU MARCHÉ MONDIAL DE L’ASSURANCE-CRÉDIT À L’EXPORTATION ? - Benmansour, Hacène (Assurances)

(untitled) (HEC Montréal, 1995)
In the context of the easing of international trade restrictions, the author examines the possibility of reorganizing credit export insurance. Three types of changes are observed in the credit market: revision of strategies, harmonization of laws and by-laws, concentration of insurers. In his conclusion, the author questions the strong competition between major credit insurers and the delicate balance between the conflicting interests of import-export consumers and credit insurers.